Development of a Mobile Robot Spatial Data Acquisition System - Ooi, Wei Han (2006)
This research focused on developing a spatial data acquisition system using mobile robot technology and close-range photogrammetry technique without ground control pointsm (G.C.Ps) on the images. Image capturing of object features and their planimetry positioning were acquired by a mobile robot and applied to create 3D plans which include contour plan, slope plan and location plan. PhotoModeler, Matlab programming and ArcView GIS software were used in the processing to create the detail plans. Additionally, the accuracy of mobile robot system was thoroughly tested and validated in real-world condition. Results showed that the coordinate accuracies computed from robot-based images in non-G.C.Ps were achieved within a range between 1.8 cm and 99 cm.